PENGARUH MOTIVASI KERJA TERHADAP PRODUKTIVITAS PEKERJA PEGAWAI DENGAN KEBERAGAMAN SEBAGAI VARIABEL MODERATING: KASUS DI KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI NTB - Hadi, Khairul (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
The purpose of this study are (1) To analyze the significance of the influence of motivation factors consisting of existence, relationship and growth on employee productivity. (2) To analyze the atmosphere of diversity in reinforcing the influence of the need for existence of work productivity of employees. (3) To analyze the atmosphere of diversity in reinforcing the influence of relationship needs to work productivity of employees. (4) To analyze the atmosphere of diversity in reinforcing the influence of growth needs on the productivity of employees in the Ministry of Religious Affairs of West Nusa Tenggara. The type of research used in this study is associative research. Data collection method used in this research is census method as much as 128 employees. The data collection tool used questionnaires and analyzed using moderating regression analysis (MRA). The results showed (1) motivation factors consisting of the needs of existence, relationship and growth have a positive and significant effect on work productivity of employees. (2) The atmosphere of diversity is able to strengthen the influence of the need for existence of work productivity of employees. (3) The atmosphere of diversity is not able to strengthen the influence of the relationship needs to work productivity of employees. (4) The atmosphere of diversity is able to strengthen the influence of growth needs on the productivity of employees in the Ministry of Religious Affairs of West Nusa Tenggara.